2019
DOI: 10.1371/journal.pone.0219348
|View full text |Cite
|
Sign up to set email alerts
|

Development of a predictive score for potentially avoidable hospital readmissions for general internal medicine patients

Abstract: Background Identifying patients at high risk of hospital preventable readmission is an essential step towards selecting those who might benefit from specific transitional interventions. Objective Derive and validate a predictive risk score for potentially avoidable readmission (PAR) based on analysis of readmissions, with a focus on medication. Design/Setting/Participants Retrospective analysis of all hospital admissions to internal medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 42 publications
2
30
1
Order By: Relevance
“…We also found that longer LOS within the index admission puts patients at risk of multiple and longer readmission events. This result is partially consistent with some other studies on internal medicine patients conducted in civilian settings (4,17,20), which examined a much shorter post-discharge period than the present study. Still, a longer LOS seems to be an important factor for predicting the risk of repeated future readmissions.…”
Section: Discussionsupporting
confidence: 94%
“…We also found that longer LOS within the index admission puts patients at risk of multiple and longer readmission events. This result is partially consistent with some other studies on internal medicine patients conducted in civilian settings (4,17,20), which examined a much shorter post-discharge period than the present study. Still, a longer LOS seems to be an important factor for predicting the risk of repeated future readmissions.…”
Section: Discussionsupporting
confidence: 94%
“…Taking beta-blocking agents, calcium channel blockers, diuretics, hypoglycaemic drugs or opioids was a significant risk for 30-day readmission. 9 Besides the higher risk of drug-related hospital readmission, some studies have also investigated the associations between combining drugs-a common practice when treating complex diseases or coexisting medical conditions-and drug-related hospital readmissions. Although using multiple drugs may be good clinical practice and compliant with guidelines for treating certain diseases, one significant consequence of combining drugs is that patients face much higher risk of ADEs, which can be caused by drug-drug interactions.…”
Section: Open Accessmentioning
confidence: 99%
“…Other factors, such as malignancy [ 31 ] and previous admission [ 32 , 33 ] were previously suggested to be related to the readmission rate. A previous study in older adults suggested that malignant solid tumour was significantly associated with 10 times higher risk for hospital admission [ 34 ].…”
Section: Discussionmentioning
confidence: 99%